The Etiologies and Clinical Characteristics of Patients Hospitalized with an Acute Febrile Illness and Central Nervous System Sydromes in Indonesia. (4th October 2017) - Aman, Abu Tholib; Gasem, Muhammad Hussein; Tjitra, Emiliana; Alisjahbana, Bachti; Kosasih, Herman; Merati, Ketut Tuti; Arif, Mansyur; Karyana, Muhammad; Sudarmono, Pratiwi; Suharto, Suharto; Lisdawati, Vivi; Neal, Aaron; et al.
Abstract: Background: Acute febrile illness is a common reason for hospitalization in many developing countries, including Indonesia. While patients can often be categorized and managed based on clinical presentations, diagnostic capacity in these countries remains limited, leading to poor patient outcomes. For patients with central nervous system (CNS) infections, identifying the underlying etiologies is particularly important to prevent lifelong neurological complications and death. Methods: As part of a study conducted at 8 top-referral hospitals across Indonesia from 2013 to 2016, 114 of 1, 486 enrolled subjects presented with an acute fever and a CNS syndrome. To identify the etiologies and clinical manifestations of these infections, as well as the management of febrile patients at the hospitals, demographic and clinical data were collected at enrollment, and blood samples were collected for diagnostic testing at enrollment, once during days 14–28, and at 3 months after enrollment. Results: Subject ages ranged from 1 to 63.2 years old (median of 4.9 years old), and underlying diseases were reported in 35 (30.7%) subjects. Standard-of-care, molecular, and serological testing identified pathogens in 56 (49.1%) cases, as detailed in the table. Of the 19 subjects who died, 18 presented with decreased consciousness and 5 were infected with Rickettsia typhi, which was clinically misdiagnosed in each case. Conclusion: The findings from this study will improve the diagnosis and treatment of patients presenting with CNS syndromes in Indonesia. Additionally, the discovery of misdiagnosed, fatal etiologies highlights the general need for greater diagnostic testing capacity to aid clinicians and inform public health policy makers. Disclosures: All authors: No reported disclosures.